Revolusi Pembelajaran Adaptif Berbasis AI dalam Pengembangan SDM dan Dampaknya terhadap Daya Saing Ekonomi - Firdaus; Pettalongi, Sagaf S.; Harianto, Jakoep Ezra (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
The advancement of artificial intelligence (AI) has driven a revolution in adaptive learning systems, playing a crucial role in human resource development (HRD). AI-based adaptive learning enables the personalization of learning methods according to individual needs, thereby enhancing efficiency and effectiveness in workforce skill development. This study aims to analyze how the implementation of AI-driven adaptive learning accelerates competency enhancement in human resources and its impact on economic competitiveness. Using a qualitative approach based on literature review and library research, this study explores various AI-based learning models applied in HRD, along with the challenges and opportunities in their implementation. The findings indicate that AI-driven adaptive learning not only improves training effectiveness but also creates a workforce that is more responsive to technological changes and industry demands. Furthermore, AI contributes to operational efficiency by reducing conventional training costs and increasing workforce productivity. However, challenges such as the digital divide, data security, and organizational readiness for AI adoption remain obstacles that need to be addressed. This study emphasizes that the adoption of AI-based adaptive learning must be supported by progressive education and labor policies to maximize its impact on a nation's economic competitiveness